High borosilicate optical lens glass and preparation process thereof

The anti-reflective layer is prepared by etching and sol coating on the surface of the high borosilicate glass, and the problem of high borosilicate glass has been solved, the effect of improving light transmittance and clarity is achieved, and the wear resistance and hydrophobic properties of the glass are enhanced.

CN119707282AActive Publication Date: 2025-03-28CHANGZHOU YONGJIA GLASS PRODUCTS CO LTD

Patent Information

Application Number
CN202411217001.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-02
Publication Date
2025-03-28
Estimated Expiration
2044-09-02

AI Technical Summary

Technical Problem

The existing high borosilicate glass has high surface reflectivity, which leads to light loss, affecting its application effect.

Method used

The anti-reflective layer was prepared on the surface of the borosilicate glass by etching and sol coating, and a porous polymer of hydrogen silane modification, fluorine-containing POSS and polyvinylpyrrolidone was used to form a hollow silica layer to reduce the refractive index of the glass surface.

Benefits of technology

It effectively reduces the reflectivity of the glass surface, improves the light transmittance and clarity, enhances the optical performance of the glass, and improves its wear-resistant and hydrophobic self-cleaning properties.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses high borosilicate optical lens glass and a preparation process thereof, and relates to the technical field of glass surface treatment.The preparation process of the high borosilicate optical lens glass comprises the following steps that raw materials are mixed, melted, formed and subjected to heat treatment, and the high borosilicate glass is obtained; and carrying out etching and sol coating to form an antireflection layer so as to obtain the optical lens glass. The preparation method comprises the following steps: preparing an antireflection layer on the surface of high borosilicate glass through etching and sol coating, during sol coating, firstly loading fluorine-containing POSS on the surface of the glass by utilizing hydrosilane to form a POSS modified layer, then preparing hollow silicon dioxide sol by taking a polymer of polyvinylpyrrolidone and fluorine-containing POSS as a template, and curing after coating to form a composite structure. The surface refractive index of the glass is greatly reduced, light reflection can be reduced, the light transmittance and definition of the glass are improved, and the visual experience is more comfortable and natural.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of glass surface treatment, in particular to a high borosilicate optical lens glass and a preparation process thereof. Background Art

[0002] Optical materials are generally divided into optical glass, optical crystals and special optical materials. Among them, optical glass is an amorphous (glassy) optical medium material that can transmit light, and is often used in the manufacture of optical components such as prisms, lenses, reflectors, windows, filters, etc. in optical instruments or optical systems. High borosilicate glass is a borosilicate glass with a silicon dioxide (SiO2) content of more than 78wt% and a boron oxide (B2O3) content of more than 10wt%. It has high strength, high hardness, low expansion coefficient and excellent thermal stability and chemical stability. However, the glass surface has a certain reflectivity, which will cause light loss, which is not conducive to its application. The existing technology achieves the effect of anti-reflection through the interference destructiveness of the thin film. According to the existing formula, when the refractive index of the glass matrix is ​​1.5, the ideal single-layer anti-reflection film should be around 1.23. However, a dense single-layer material cannot have such a low refractive index. Therefore, we propose a high borosilicate optical lens glass and its preparation process. Summary of the invention

[0003] The object of the present invention is to provide a high borosilicate optical lens glass and a preparation process thereof to solve the problems raised in the above background technology.

[0004] In order to solve the above technical problems, the present invention provides the following technical solutions: A preparation process of high borosilicate optical lens glass, comprising the following processes:

[0005] The raw materials are mixed, melted, molded, and heat-treated to obtain high borosilicate glass;

[0006] Etching and sol coating are performed to form an anti-reflection layer to obtain optical lens glass.

[0007] Furthermore, the raw materials include the following components by mass: 78 to 85 parts of silicon dioxide, 10 to 15 parts of boron oxide, 5 to 10 parts of borax, 3 to 6 parts of sodium oxide, 2 to 10 parts of sodium silicate, 2.0 to 4.5 parts of aluminum hydroxide, 1 to 3 parts of zirconium phosphate, 0.1 to 0.5 parts of lithium oxide, and 0.065 to 0.075 parts of cerium dioxide.

[0008] In the above technical scheme, silicon dioxide and boron oxide serve as the skeleton of glass and are the main preparation components. Borax (Na2B4O7·10H2O) is thermally decomposed in the melting process to form boron oxide (B2O3), sodium oxide (Na2O) and water. Boric acid is thermally decomposed to produce boron oxide (B2O3) and water. Sodium silicate (Na2SiO3) is thermally decomposed to produce silicon dioxide (SiO2) and sodium oxide. Aluminum hydroxide is thermally decomposed to form aluminum oxide (Al2O3) and water. Boron oxide, sodium oxide and silicon dioxide are the basic components to form borosilicate glass, which has a low expansion coefficient, high thermal stability and chemical stability. Sodium oxide plays the role of a solvent, provides free oxygen, and changes the structure of boron oxide from layered to frame-like, making it easier to form a uniform melt with silicon oxide, which has the effect of promoting the melting of glass components, adjusting the refractive index of glass, and improving its strength and chemical stability. Boric acid can reduce the melting point and viscosity of glass, promote the flow and forming of molten glass, improve the physical and chemical properties of glass, and improve its transparency, heat resistance and corrosion resistance. The water produced is converted into water vapor and released in the high-temperature melting process, which can carry the bubbles in the molten glass out and produce a clarification effect; it cooperates with cerium dioxide (CeO2) in the raw material to play a staged clarification role. The decomposition temperature of cerium dioxide is higher. It decomposes at high temperature to generate cerium trioxide (Ce203), and releases oxygen, which accelerates clarification and realizes the homogenization of molten glass; at the same time, the ionic compound cerium trioxide has the effects of high field strength, high coordination and high accumulation, which makes the structure of the produced glass tend to be dense, thereby helping to improve its mechanical properties and thermal stability. While improving the chemical stability, thermal stability and hardness of glass, aluminum oxide can also increase its refractive index and improve the optical properties of glass. Lithium oxide (LiO2) can play a solubilizing role, reduce the thermal expansion coefficient of glass, and improve its chemical stability and thermal stability. Lithium has the smallest ion radius and can easily enter the glass network structure to form ion exchange. Due to its high electronegativity, it attracts surrounding molecules, making the glass denser and improving the gloss and hardness of the glass. Zirconium phosphate has the common characteristics of layered compounds, with high specific surface area and surface charge, ion exchange characteristics and adsorption capacity, and can exchange ions with lithium oxide, strengthen the connection between glass components, and improve the thermal stability, chemical stability and strength of the glass.

[0009] Furthermore, the mixed melting process is as follows: heating the raw materials to 1400-1550° C. to melt, and keeping the temperature for 30-60 minutes; heating to 1600-1700° C., introducing oxygen, and melting for 1-3 hours;

[0010] The oxygen flow rate is 0.5 to 3.0 L / min, and the oxygen flow time is 10 to 60 minutes.

[0011] In the above technical solution, the raw materials are melted at a relatively low temperature to allow the raw materials to react and effectively avoid volatilization of the raw materials. Then the temperature is raised to reduce the viscosity of the glass liquid, and the oxygen introduced can be bubbled evenly, which is conducive to the homogenization of the composition, structure and quality of the produced high borosilicate glass.

[0012] Furthermore, the molding adopts the leaking molding technology, which has a higher raw material utilization rate and a better optical quality of the produced high borosilicate glass.

[0013] Furthermore, the heat treatment process is as follows: keeping the temperature at 540-650° C. for 1-3 hours; and naturally cooling to room temperature.

[0014] In the above technical solution, the obtained high borosilicate glass is annealed to eliminate the residual stress in the glass, promote its optical and structural homogenization, and improve the stability of the glass.

[0015] Furthermore, the etching process is as follows:

[0016] The high borosilicate glass is placed in an etching solution, and subjected to a hydrothermal reaction at a temperature of 158 to 162° C. for 450 to 500 minutes; after the reaction, the glass is taken out, washed, and dried to form an etching layer.

[0017] Further, in step S1, the etching solution includes the following mass components: 3.0-22.5 g / L disodium ethylenediaminetetraacetate, 5.5-35 g / L tetrasodium ethylenediaminetetraacetate;

[0018] The mass ratio of disodium ethylenediaminetetraacetate to tetrasodium ethylenediaminetetraacetate is (30-45):(55-70).

[0019] In the above technical scheme, the obtained high borosilicate glass is surface etched using disodium ethylenediaminetetraacetate and tetrasodium ethylenediaminetetraacetate. The above two components are acidic and alkaline in water respectively. By controlling the amount of disodium ethylenediaminetetraacetate and tetrasodium ethylenediaminetetraacetate, the pH value of the etching solution can be regulated, and it has a strong complexing ability to stabilize the etching process. Under hydrothermal conditions, the etching solution components exchange ions with the high borosilicate glass to form holes on the glass surface, the porosity of the glass surface increases, the refractive index of the prepared etching layer decreases, and the reflectivity of the glass surface is reduced by interference destructive, thereby improving its transmittance.

[0020] Further, the sol coating process is as follows:

[0021] The etched borosilicate glass is modified with hydrogen silane; fluorine-containing POSS is prepared with monofluorotriethoxysilane and alkenylsiloxane as raw materials; dichloromethane and photoinitiator are added to prepare a fluorine-containing POSS / dichloromethane dispersion; the borosilicate glass obtained in the previous step is added and irradiated with ultraviolet light to form a POSS modification layer;

[0022] Take fluorine-containing POSS and polyvinyl pyrrolidone, mix them in a solvent, add an initiator, and heat to react; then add tetraethyl orthosilicate, ammonia water, and anhydrous ethanol to react to obtain a sol; immerse, pull, and calcine the high borosilicate glass obtained in the previous step to form a hollow silica layer to obtain an anti-reflection layer.

[0023] Further, the sol coating process is as follows:

[0024] (1) placing the etched borosilicate glass in a hydrogen silane / ethanol solution and subjecting it to ultrasonic treatment for 20 to 30 minutes; taking it out, and hydrolyzing it at a temperature of 23 to 27° C. and a humidity of 40% to 50% for 18 to 24 hours to form a hydrogen silane modification layer;

[0025] (2) Mixing monofluorotriethoxysilane, alkenylsiloxane, ethanol, hydrochloric acid and deionized water, heating to 70-80° C., stirring and reflux reaction for 5-12 hours; cooling to room temperature, and continuing the reaction for 15-24 hours; recrystallizing from a mixed solution of tetrahydrofuran and methanol, filtering, washing and drying to obtain fluorinated POSS; adding dichloromethane and a photoinitiator to prepare a fluorinated POSS / dichloromethane dispersion;

[0026] The high borosilicate glass obtained in the previous step is placed in a fluorine-containing POSS / dichloromethane dispersion and irradiated with ultraviolet light for 10 to 50 minutes; then placed at a temperature of 150 to 160° C. and cured for 100 to 150 minutes; washed and dried to form a POSS modified layer;

[0027] (3) deionized water, fluorinated POSS and polyvinyl pyrrolidone are mixed, heated to 28-82° C., an initiator is added, and the reaction is carried out for 1-15 hours; ammonia water and anhydrous ethanol are added, and at a temperature of 68-72° C., ethyl orthosilicate is slowly added and stirred for 10-12 hours to obtain a sol;

[0028] The high borosilicate glass obtained in the previous step is immersed in the sol for 6 to 10 minutes, and then pulled out at a pulling speed of 70 to 80 cm / min; it is placed at room temperature for 10 to 15 minutes to volatilize the alcohol; it is placed at 60 to 70°C for drying for 8 to 12 hours, and calcined at 400 to 500°C for 2 to 3 hours to form a hollow silica layer to obtain an anti-reflection layer.

[0029] Furthermore, in step (1), the concentration of the hydrogen silane / ethanol solution is 3-5v%; the hydrogen silane is one of triethoxysilane and trimethoxysilane.

[0030] Furthermore, in step (2), the mass ratio of monofluorotriethoxysilane, alkenylsiloxane, ethanol, deionized water, and hydrochloric acid is (67-80):(14-58):100:(12-16):(7.5×10-4 ~8.3×10 -4 );

[0031] Hydrochloric acid was added in the form of 0.12 M dilute hydrochloric acid.

[0032] Further, in step (2), the concentration of the fluorine-containing POSS / dichloromethane dispersion is 5 to 15 wt %;

[0033] The photoinitiator is Irgacure 2959, and the amount used is 5% by mass of the fluorinated POSS.

[0034] Furthermore, in step (2), the alkenylsiloxane is one of methylvinyldimethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, γ-(methacryloyloxy)propyltrimethoxysilane, γ-(methacryloyloxy)propyltriethoxysilane, and γ-(methacryloyloxy)propylmethyldimethoxysilane.

[0035] Further, in step (3), the sol is prepared from the following components: by mass, 2.5-3.0 parts of fluorine-containing POSS, 0.3-0.4 parts of polyvinyl pyrrolidone, 0.1-0.2 parts of initiator, 6-8 parts of ammonia water, 5-6 parts of tetraethyl orthosilicate, 100-120 parts of anhydrous ethanol and 45-50 parts of deionized water;

[0036] The initiator is one of aluminum chloride and ammonium persulfate.

[0037] In the above technical scheme, fluorine-containing siloxane is mixed with alkenyl siloxane, and POSS (cage-type polysilsesquioxane) is formed under the catalysis of acid. The structure of the POSS contains fluorine and alkenyl groups, which can effectively reduce the refractive index of the prepared POSS and give it reactivity. Hydrogen silane is used to modify the pores on the surface of the etched high borosilicate glass. Under the action of an initiator and irradiation, the addition of silicon-hydrogen bonds and alkenyl groups is used to achieve the loading of POSS on the glass surface, and the pores are further modified and filled to form a POSS modified layer, which has low reflection characteristics and further reduces the reflectivity; at the same time, the POSS modified layer has good mechanical strength, hardness and hydrophobicity, which helps to maintain the morphology of the etching layer for a long time and improve the surface performance of the prepared glass.

[0038] Fluorinated POSS is mixed with polyvinyl pyrrolidone, fluorinated POSS is adsorbed with polyvinyl pyrrolidone by electrostatic action, and under the action of initiator, polymerization occurs to form porous polymer, as template, tetraethyl orthosilicate infiltration, and hydrolyzed under the action of ammonia, polymerized on the template surface, forming hollow silica and sol doped with fluorinated POSS porous polymer, its refractive index is low. It is applied to the surface of high borosilicate glass (POSS modified layer) after POSS modification and then solidified to form a hollow silica layer, so far completing the preparation of glass surface anti-reflection layer. By the multilayer structure compound of etching layer, POSS modified layer and hollow silica layer, the refractive index of high borosilicate surface film layer is greatly reduced, and the glass made has effective anti-reflection ability, can reduce the reflection of light, improve the light transmittance and clarity of glass, make visual experience more comfortable, natural. Meanwhile, the doping of fluorinated POSS porous polymer makes the made anti-reflection layer have higher strength, hardness and hydrophobicity, realizes wear-resistant, easy to clean.

[0039] Compared with the prior art, the present invention has the following beneficial effects:

[0040] The invention discloses a preparation process of a high-borosilicate optical lens glass. The anti-reflection layer is prepared on the surface of the high-borosilicate glass by etching and sol coating. The sol coating first uses hydrogen silane to load fluorine-containing POSS on the glass surface to form a POSS modification layer. Then, a hollow silica sol is prepared using polyvinyl pyrrolidone and a fluorine-containing POSS polymer as a template. After coating, the sol is cured to form a composite structure, so that the refractive index of the glass surface is greatly reduced, the reflection of light can be reduced, the light transmittance and clarity of the glass are improved, and the visual experience is more comfortable and natural. DETAILED DESCRIPTION

[0041] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0042] In the following specific implementations,

[0043] In Examples 1-3, the raw materials include the following components by mass: 80 parts of silicon dioxide, 12 parts of boron oxide, 7 parts of borax, 4 parts of sodium oxide, 8 parts of sodium silicate, 3.5 parts of aluminum hydroxide, 1 part of zirconium phosphate, 0.2 parts of lithium oxide, and 0.07 parts of cerium dioxide;

[0044] The photoinitiator was Irgacure 2959, and the amount used was 5% by mass of fluorinated POSS;

[0045] The initiator is ammonium persulfate.

[0046] Embodiment 1: A process for preparing high borosilicate optical lens glass, comprising the following processes:

[0047] 1. Heat the raw materials to 1400℃ and melt them, keep them warm for 60min; heat them to 1600℃, introduce oxygen, and melt them for 3h; the oxygen flow rate is 0.5L / min, and the introduction time is 60min; leak the materials to form, keep them warm for 3h at 540℃; cool them naturally to room temperature to obtain high borosilicate glass;

[0048] 2. Place the high borosilicate glass in an etching solution and perform a hydrothermal reaction at 158°C for 450 minutes; after the reaction, take out, wash, and dry to form an etching layer; the etching solution includes the following mass components: 3.0 g / L disodium ethylenediaminetetraacetate and 7.0 g / L tetrasodium ethylenediaminetetraacetate;

[0049] 3.1 Place the etched borosilicate glass in a 3v% triethoxysilane / ethanol solution and ultrasonicate for 20 minutes; take it out and hydrolyze it at 23°C and 40% humidity for 18 hours to form a hydrogen silane modification layer;

[0050] 3.2 Mix fluorotriethoxysilane, methylvinyldimethoxysilane, ethanol, hydrochloric acid (0.12M dilute hydrochloric acid) and deionized water, heat to 70°C, stir and reflux for 5h; cool to room temperature and continue to react for 15h; recrystallize from a mixed solution of tetrahydrofuran and methanol, filter, wash and dry to obtain fluorinated POSS; add dichloromethane and photoinitiator to prepare a fluorinated POSS / dichloromethane dispersion with a concentration of 5wt%; the mass ratio of fluorotriethoxysilane, alkenylsiloxane, ethanol, deionized water and hydrochloric acid is 67:14.3:100:12:7.5×10 -4 ;

[0051] The high borosilicate glass obtained in the previous step is placed in a fluorine-containing POSS / dichloromethane dispersion and irradiated with ultraviolet light for 10 minutes; then taken out, placed at 150° C., and cured for 100 minutes; washed and dried to form a POSS modified layer;

[0052] 3.3 Mix deionized water, fluorinated POSS and polyvinyl pyrrolidone, heat to 78°C, add initiator, and react for 9 hours; add ammonia water and anhydrous ethanol, slowly add tetraethyl orthosilicate at 68°C, add within 30 minutes, stir for 10 hours, and obtain a sol; the sol is prepared from the following components: by mass, 2.5 parts of fluorinated POSS, 0.3 parts of polyvinyl pyrrolidone, 0.1 parts of initiator, 6 parts of ammonia water, 5 parts of tetraethyl orthosilicate, 100 parts of anhydrous ethanol and 45 parts of deionized water;

[0053] The high borosilicate glass obtained in the previous step was immersed in the sol for 6 minutes, and then pulled out at a pulling speed of 70 cm / min; it was placed at room temperature for 10 minutes to volatilize the alcohol; it was dried at 60°C for 8 hours, and calcined at 400°C for 3 hours to form a hollow silica layer, obtain an anti-reflection layer, and obtain an optical lens glass.

[0054] Embodiment 2: A process for preparing high borosilicate optical lens glass, comprising the following processes:

[0055] 1. Heat the raw materials to 1475℃ and melt them, keep them warm for 45min; heat them to 1650℃, introduce oxygen, and melt them for 2h; the oxygen flow rate is 1.8L / min, and the introduction time is 30min; leak the materials into shape, keep them warm for 2h at 600℃; cool them naturally to room temperature to obtain high borosilicate glass;

[0056] 2. Place the high borosilicate glass in an etching solution and perform a hydrothermal reaction at 160°C for 475 minutes; after the reaction, take out, wash, and dry to form an etching layer; the etching solution includes the following mass components: 13g / L disodium ethylenediaminetetraacetate and 20g / L tetrasodium ethylenediaminetetraacetate;

[0057] 3.1 Place the etched borosilicate glass in a 4v% trimethoxysilane / ethanol solution and ultrasonicate for 25 minutes; take it out and hydrolyze it at 25°C and 45% humidity for 21 hours to form a hydrogen silane modification layer;

[0058] 3.2 Mix fluorotriethoxysilane, vinyl triethoxysilane, ethanol, hydrochloric acid (0.12M dilute hydrochloric acid) and deionized water, heat to 75°C, stir and reflux for 8h; cool to room temperature and continue to react for 20h; recrystallize from a mixed solution of tetrahydrofuran and methanol, filter, wash and dry to obtain fluorinated POSS; add dichloromethane and photoinitiator to prepare a fluorinated POSS / dichloromethane dispersion with a concentration of 10wt%; the mass ratio of fluorotriethoxysilane, alkenyl siloxane, ethanol, deionized water and hydrochloric acid is 72:28.7:100:14:8.0×10 -4 ;

[0059] The high borosilicate glass obtained in the previous step is placed in a fluorine-containing POSS / dichloromethane dispersion and irradiated with ultraviolet light for 30 minutes; then taken out, placed at 155° C., and cured for 120 minutes; washed and dried to form a POSS modified layer;

[0060] 3.3 Mix deionized water, fluorinated POSS and polyvinyl pyrrolidone, heat to 80°C, add initiator, and react for 12 hours; add ammonia water and anhydrous ethanol, slowly add tetraethyl orthosilicate at 70°C and stir for 11 hours to obtain a sol; the sol is prepared from the following components: by mass, 2.8 parts of fluorinated POSS, 0.35 parts of polyvinyl pyrrolidone, 0.15 parts of initiator, 7 parts of ammonia water, 5.5 parts of tetraethyl orthosilicate, 110 parts of anhydrous ethanol and 48 parts of deionized water;

[0061] The high borosilicate glass obtained in the previous step was immersed in the sol for 8 minutes, and then pulled out at a pulling speed of 75 cm / min; it was placed at room temperature for 12 minutes to volatilize the alcohol; it was dried at 65°C for 10 hours, and calcined at 450°C for 2.5 hours to form a hollow silica layer, obtain an anti-reflection layer, and obtain an optical lens glass.

[0062] Embodiment 3: A process for preparing high borosilicate optical lens glass, comprising the following processes:

[0063] 1. Heat the raw materials to 1550℃ and melt them, keep them warm for 30min; heat them to 1700℃, introduce oxygen, and melt them for 1h; the oxygen flow rate is 3.0L / min, and the introduction time is 10min; leak the materials into shape, keep them warm for 1h at 650℃; cool them naturally to room temperature to obtain high borosilicate glass;

[0064] 2. Place the high borosilicate glass in an etching solution and perform a hydrothermal reaction at 162°C for 500 minutes; after the reaction, take out, wash, and dry to form an etching layer; the etching solution includes the following mass components: 22.5 g / L disodium ethylenediaminetetraacetate and 35 g / L tetrasodium ethylenediaminetetraacetate;

[0065] 3.1 Place the etched borosilicate glass in a 5v% triethoxysilane / ethanol solution and ultrasonicate for 30 minutes; take it out and hydrolyze it at 27°C and 50% humidity for 24 hours to form a hydrogen silane modification layer;

[0066] 3.2 Mix monofluorotriethoxysilane, γ-(methacryloyloxy)propyltriethoxysilane, ethanol, hydrochloric acid (0.12M dilute hydrochloric acid) and deionized water, heat to 80°C, stir and reflux for 12h; cool to room temperature and continue to react for 24h; recrystallize from a mixed solution of tetrahydrofuran and methanol, filter, wash and dry to obtain fluorinated POSS; add dichloromethane and photoinitiator to prepare a fluorinated POSS / dichloromethane dispersion with a concentration of 15wt%; the mass ratio of monofluorotriethoxysilane, alkenylsiloxane, ethanol, deionized water and hydrochloric acid is 80:58:100:16:8.3×10 -4 ;

[0067] The high borosilicate glass obtained in the previous step is placed in a fluorine-containing POSS / dichloromethane dispersion and irradiated with ultraviolet light for 50 minutes; then taken out, placed at 160° C. and cured for 150 minutes; washed and dried to form a POSS modified layer;

[0068] 3.3 Mix deionized water, fluorinated POSS and polyvinyl pyrrolidone, heat to 82°C, add initiator, and react for 15h; add ammonia water and anhydrous ethanol, slowly add tetraethyl orthosilicate at 72°C and stir for 12h to obtain a sol; the sol is prepared from the following components: by mass, 3.0 parts of fluorinated POSS, 0.4 parts of polyvinyl pyrrolidone, 0.2 parts of initiator, 8 parts of ammonia water, 6 parts of tetraethyl orthosilicate, 120 parts of anhydrous ethanol and 50 parts of deionized water;

[0069] The high borosilicate glass obtained in the previous step was immersed in the sol for 10 minutes, and then pulled out at a pulling speed of 80 cm / min; it was placed at room temperature for 15 minutes to volatilize the alcohol; it was dried at 70°C for 12 hours, and calcined at 500°C for 2 hours to form a hollow silica layer, to obtain an anti-reflection layer, and to obtain an optical lens glass.

[0070] Comparative Example 1: A process for preparing high borosilicate optical lens glass, comprising the following processes:

[0071] Process 1-2 is the same as that in Example 1, and high borosilicate glass and its surface etching layer are obtained in sequence;

[0072] Steps 3.1 and 3.2 are the same as those in Example 1, forming a POSS modified layer;

[0073] 3.3 Mix deionized water, styrene and polyvinyl pyrrolidone, heat to 78°C, add initiator, and react for 9 hours; add ammonia water and anhydrous ethanol, slowly add tetraethyl orthosilicate at 68°C, add within 30 minutes, stir for 10 hours, and obtain a sol; the sol is prepared from the following components: by mass, 2.5 parts of styrene, 0.3 parts of polyvinyl pyrrolidone, 0.1 parts of initiator, 6 parts of ammonia water, 5 parts of tetraethyl orthosilicate, 100 parts of anhydrous ethanol and 45 parts of deionized water;

[0074] The high borosilicate glass obtained in the previous step was immersed in the sol for 6 minutes, and then pulled out at a pulling speed of 70 cm / min; placed at room temperature for 10 minutes to volatilize the alcohol; dried at 60°C for 8 hours, and calcined at 400°C for 3 hours to form a hollow silica layer, obtain an anti-reflection layer, and obtain an optical lens glass;

[0075] Steps 3.1 and 3.3 are the same as those in Example 1, forming an anti-reflection layer to obtain an optical lens glass.

[0076] Comparative Example 2: A process for preparing high borosilicate optical lens glass, comprising the following processes:

[0077] Process 1-2 is the same as that in Example 1, and high borosilicate glass and its surface etching layer are obtained in sequence;

[0078] 3.2 Mix methylvinyldimethoxysilane, ethanol, hydrochloric acid (0.12M dilute hydrochloric acid) and deionized water, heat to 70°C, stir and reflux for 5h; cool to room temperature and continue to react for 15h; recrystallize from a mixed solution of tetrahydrofuran and methanol, filter, wash and dry to obtain fluorinated POSS; add dichloromethane and photoinitiator to prepare a fluorinated POSS / dichloromethane dispersion with a concentration of 5wt%; the mass ratio of alkenylsiloxane, ethanol, deionized water and hydrochloric acid is 58:100:12:7.5×10 -4 ;

[0079] The high borosilicate glass obtained in the previous step is placed in a fluorine-containing POSS / dichloromethane dispersion and irradiated with ultraviolet light for 10 minutes; then taken out, placed at 150° C., and cured for 100 minutes; washed and dried to form a POSS modified layer;

[0080] Steps 3.1 and 3.3 are the same as those in Comparative Example 1, forming an anti-reflection layer to obtain an optical lens glass.

[0081] Comparative Example 3: A process for preparing high borosilicate optical lens glass, comprising the following processes:

[0082] Process 1-2 is the same as that in Example 1, and high borosilicate glass and its surface etching layer are obtained in sequence;

[0083] 3. Mix deionized water, styrene and polyvinyl pyrrolidone, heat to 78°C, add initiator, and react for 9 hours; add ammonia water and anhydrous ethanol, slowly add tetraethyl orthosilicate at 68°C, add within 30 minutes, stir for 10 hours, and obtain a sol; the sol is prepared from the following components: by mass, 2.5 parts of styrene, 0.3 parts of polyvinyl pyrrolidone, 0.1 parts of initiator, 6 parts of ammonia water, 5 parts of tetraethyl orthosilicate, 100 parts of anhydrous ethanol and 45 parts of deionized water;

[0084] The high borosilicate glass obtained in the previous step was immersed in the sol for 6 minutes, and then pulled out at a pulling speed of 70 cm / min; it was placed at room temperature for 10 minutes to volatilize the alcohol; it was dried at 60°C for 8 hours, and calcined at 400°C for 3 hours to form a hollow silica layer, obtain an anti-reflection layer, and obtain an optical lens glass.

[0085] Comparative Example 4: A process for preparing high borosilicate optical lens glass, comprising the following processes:

[0086] Process 1 is the same as in Example 1, obtaining high borosilicate glass;

[0087] 2. Mix deionized water, styrene and polyvinyl pyrrolidone, heat to 78°C, add initiator, and react for 9 hours; add ammonia water and anhydrous ethanol, slowly add tetraethyl orthosilicate at 68°C, add within 30 minutes, stir for 10 hours, and obtain a sol; the sol is prepared from the following components: by mass, 2.5 parts of styrene, 0.3 parts of polyvinyl pyrrolidone, 0.1 parts of initiator, 6 parts of ammonia water, 5 parts of tetraethyl orthosilicate, 100 parts of anhydrous ethanol and 45 parts of deionized water;

[0088] The high borosilicate glass obtained in the previous step was immersed in the sol for 6 minutes, and then pulled out at a pulling speed of 70 cm / min; it was placed at room temperature for 10 minutes to volatilize the alcohol; it was dried at 60°C for 8 hours, and calcined at 400°C for 3 hours to form a hollow silica layer, obtain an anti-reflection layer, and obtain an optical lens glass.

[0089] Comparative Example 5: A process for preparing high borosilicate optical lens glass, comprising the following processes:

[0090] Process 1 is the same as in Example 1, obtaining high borosilicate glass;

[0091] 2. Place the high borosilicate glass in an etching solution and perform a hydrothermal reaction at 158°C for 450 minutes; take out the glass after the reaction, wash it, and dry it to form an etching layer; the etching solution includes the following mass components: 3.0 g / L disodium ethylenediaminetetraacetate and 7.0 g / L tetrasodium ethylenediaminetetraacetate; an anti-reflection layer is obtained to obtain an optical lens glass.

[0092] Experiment: Take the optical lens glasses obtained in Examples 1-3 and Comparative Examples 1-5, prepare samples, test their properties respectively and record the test results:

[0093] Optical performance test: The transmittance of the sample was tested using a UV-visible spectrometer with an experimental wavelength of 400-800nm;

[0094] Hardness test: Use a pencil hardness tester and GB / T 6739 as the reference standard to test the surface hardness of the sample. The test load is 750g and the test angle is 45°. The test is carried out until a scratch exceeding 3mm appears on the surface of the sample. The maximum pencil hardness that fails to cause a scratch exceeding 3mm on the surface of the sample is used as the characterization data.

[0095] Wear resistance test: Use a steel wool abrasion tester to rub the sample surface back and forth 100 times, with a test load of 500g. After the test, test the transmittance of the sample again and calculate the change in transmittance before and after the test.

[0096] Hydrophobic performance test: A contact angle meter was used to measure the contact angle of the sample surface. The static contact angle of the water droplet was used as the characterization data. The experimental water droplet was 4 μL.

[0097] Transmittance (%) hardness Contact angle (°) Transmittance decrease (%) Example 1 98.2 7H 150.4 0.43 Example 2 98.5 9H 153.5 0.30 Example 3 98.0 9H 157.1 0.14 Comparative Example 1 97.3 6H 145.4 0.74 Comparative Example 2 96.2 6H 144.0 0.66 Comparative Example 3 97.8 3H 142.8 1.05 Comparative Example 4 93.4 4H 128.5 0.90 Comparative Example 5 97.2 2H 121.7 1.78

[0098] According to the data in the above table, we can clearly draw the following conclusions:

[0099] The optical lens glasses obtained in Examples 1-3 are compared with the optical lens glasses obtained in Comparative Examples 1-5. The test results show that:

[0100] Compared with the comparative example, the optical lens glass obtained in Examples 1-3 has higher transmittance, hardness and contact angle data and lower transmittance decrease, which fully demonstrates that the present invention achieves the improvement of the optical performance, wear resistance and hydrophobic self-cleaning performance of the optical lens glass.

[0101] Compared with Example 1, the colloidal sol in Comparative Example 1 is prepared by styrene, polyvinyl pyrrolidone, tetraethyl orthosilicate, etc., and fluorine-containing POSS is replaced by styrene. On the basis of Comparative Example 1, the POSS in Comparative Example 2 is vinyl POSS. Compared with Example 1, the POSS modifying layer is not set in Comparative Example 3. Compared with Comparative Example 3, the high borosilicate glass in Comparative Example 4 is not etched, and the optical lens glass is composed of high borosilicate glass and a hollow silica layer. The optical lens glass in Comparative Example 5 is obtained by etching high borosilicate glass. The optical lens glass obtained in Comparative Examples 1-5, its transmittance, hardness, contact angle, transmittance decline amplitude fail to maintain a better level at the same time. It can be known that the present invention can promote the comprehensive improvement of its optical performance, wear resistance, and hydrophobic self-cleaning performance to the setting of the optical lens glass process and its used components.

[0102] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

Claims

1. A process for preparing high borosilicate optical lens glass, characterized in that: Including the following processes: The raw materials are mixed, melted, molded, and heat-treated to obtain high borosilicate glass; Etching, sol coating, forming an anti-reflection layer, and obtaining an optical lens glass; the sol coating process is as follows: The etched borosilicate glass is modified with hydrogen silane; fluorine-containing POSS is prepared with monofluorotriethoxysilane and alkenylsiloxane as raw materials; dichloromethane and photoinitiator are added to prepare a fluorine-containing POSS / dichloromethane dispersion; the borosilicate glass obtained in the previous step is added and irradiated with ultraviolet light to form a POSS modification layer; Take fluorine-containing POSS and polyvinyl pyrrolidone, mix them in a solvent, add an initiator, and heat to react; then add tetraethyl orthosilicate, ammonia water, and anhydrous ethanol to react to obtain a sol; immerse the high borosilicate glass obtained in the previous step in the sol, pull, and calcine to form a hollow silica layer to obtain an anti-reflection layer.

2. The process for preparing a high borosilicate optical lens glass according to claim 1, characterized in that: The raw materials include the following components by mass: 78-85 parts of silicon dioxide, 10-15 parts of boron oxide, 5-10 parts of borax, 3-6 parts of sodium oxide, 2-10 parts of sodium silicate, 2.0-4.5 parts of aluminum hydroxide, 1-3 parts of zirconium phosphate, 0.1-0.5 parts of lithium oxide, and 0.065-0.075 parts of cerium dioxide.

3. The process for preparing a high borosilicate optical lens glass according to claim 1, characterized in that: The mixed melting process is as follows: heating the raw materials to 1400-1550° C. to melt, and keeping the temperature for 30-60 minutes; heating to 1600-1700° C., introducing oxygen, and melting for 1-3 hours; the oxygen flow rate is 0.5-3.0 L / min, and the introduction time is 10-60 minutes.

4. The process for preparing a high borosilicate optical lens glass according to claim 1, characterized in that: The heat treatment process is as follows: keeping the temperature at 540-650° C. for 1-3 hours; and cooling naturally.

5. The process for preparing a high borosilicate optical lens glass according to claim 1, characterized in that: The etching process is as follows: placing high borosilicate glass in an etching solution, and performing a hydrothermal reaction at a temperature of 158 to 162° C. for 450 to 500 minutes to form an etching layer; the etching solution includes the following mass components: 3.0 to 22.5 g / L disodium ethylenediaminetetraacetate and 5.5 to 35 g / L tetrasodium ethylenediaminetetraacetate; the mass ratio of disodium ethylenediaminetetraacetate to tetrasodium ethylenediaminetetraacetate is (30 to 45):(55 to 70).

6. The process for preparing a high borosilicate optical lens glass according to claim 1, characterized in that: The sol coating process is as follows: (1) placing the etched borosilicate glass in a hydrogen silane / ethanol solution and subjecting it to ultrasonic treatment for 20 to 30 minutes; taking it out, and hydrolyzing it at a temperature of 23 to 27° C. and a humidity of 40% to 50% for 18 to 24 hours to form a hydrogen silane modification layer; (2) mixing monofluorotriethoxysilane, alkenylsiloxane, ethanol, hydrochloric acid and deionized water, heating to 70-80° C., stirring and reflux reaction for 5-12 hours; cooling to room temperature, continuing the reaction for 15-24 hours to obtain fluorine-containing POSS; adding dichloromethane and a photoinitiator to prepare a fluorine-containing POSS / dichloromethane dispersion; The high borosilicate glass obtained in the previous step is placed in a fluorine-containing POSS / dichloromethane dispersion and irradiated with ultraviolet light for 10 to 50 minutes; then placed at a temperature of 150 to 160° C. and cured for 100 to 150 minutes to form a POSS modification layer; (3) deionized water, fluorinated POSS and polyvinyl pyrrolidone are mixed, heated to 28-82° C., an initiator is added, and the reaction is carried out for 1-15 hours; ammonia water and anhydrous ethanol are added, and at a temperature of 68-72° C., ethyl orthosilicate is slowly added and stirred for 10-12 hours to obtain a sol; The high borosilicate glass obtained in the previous step is immersed in the sol for 6 to 10 minutes, and then pulled out at a pulling speed of 70 to 80 cm / min; it is placed at room temperature for 10 to 15 minutes, dried at 60 to 70°C for 8 to 12 hours, and calcined at 400 to 500°C for 2 to 3 hours to form a hollow silica layer to obtain an anti-reflection layer.

7. The process for preparing a high borosilicate optical lens glass according to claim 6, characterized in that: In step (1), the concentration of the hydrogen silane / ethanol solution is 3-5v%; the hydrogen silane is one of triethoxysilane and trimethoxysilane.

8. The process for preparing a high borosilicate optical lens glass according to claim 6, characterized in that: In step (2), the mass ratio of monofluorotriethoxysilane, alkenylsiloxane, ethanol, deionized water and hydrochloric acid is (67-80):(14-58):100:(12-16):(7.5×10 -4 ~8.3×10 -4 ).

9. The process for preparing a high borosilicate optical lens glass according to claim 6, characterized in that: In step (3), the sol is prepared from the following components: by mass, 2.5-3.0 parts of fluorine-containing POSS, 0.3-0.4 parts of polyvinyl pyrrolidone, 0.1-0.2 parts of initiator, 6-8 parts of ammonia water, 5-6 parts of tetraethyl orthosilicate, 100-120 parts of anhydrous ethanol and 45-50 parts of deionized water.

10. A high borosilicate optical lens glass obtained according to the preparation process according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Preparation method of multivariant complexing etching liquid used for magnesium alloy surface treatment

    CN101538717A

  • Method used for increasing silicon dioxide antireflection film hole stability

    CN104609738A

  • Polyhedral oligomeric silsesquioxane (POSS) nano hybrid molecular compound containing multiple silyl phenyl groups and application thereof

    CN109651616A

  • Preparation method of stable perfluorohexyl functionalized active POSS-based super-amphiphobic coating modified cotton fabric

    CN113832732A

  • Self-repairing and self-cleaning glass waterproof agent as well as preparation method and application thereof

    CN116282943A

Cited By

  • Wear-resistant anti-fingerprint glass cover plate for display screen and preparation process of wear-resistant anti-fingerprint glass cover plate

    CN121063831A

  • A wear-resistant anti-fingerprint glass cover plate for display screen and a preparation process thereof

    CN121063831B